2021
DOI: 10.3390/cancers13225803
|View full text |Cite
|
Sign up to set email alerts
|

Does Pancreatic Fistula Affect Long-Term Survival after Resection for Pancreatic Cancer? A Systematic Review and Meta-Analysis

Abstract: Background: The impact of postoperative pancreatic fistula (POPF) on survival after resection for pancreatic ductal adenocarcinoma (PDAC) remains unclear. Methods: The MEDLINE, Scopus, Embase, Web of Science, and Cochrane Library databases were searched for studies reporting on survival in patients with and without POPF. A meta-analysis was performed to investigate the impact of POPF on disease-free survival (DFS) and overall survival (OS). Results: Sixteen retrospective cohort studies concerning a total of 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…TP-IAT should be further considered in light of the latest evidence of the impact of POPF on the long-term outcome. 40 , 41 In fact, TP may prevent a long-lasting decline of patients’ general condition associated with CR-POPF. This is particularly relevant in patients with adenocarcinoma, where a complicated clinical course may delay the start of adjuvant therapy, impacting oncological outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TP-IAT should be further considered in light of the latest evidence of the impact of POPF on the long-term outcome. 40 , 41 In fact, TP may prevent a long-lasting decline of patients’ general condition associated with CR-POPF. This is particularly relevant in patients with adenocarcinoma, where a complicated clinical course may delay the start of adjuvant therapy, impacting oncological outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Our results further support this possibility, since IAT was able to provide partial insulin secretion in around 90% of patients undergoing TP, with good metabolic control (HbA1c level of ≤7.5%39) in 62% of subjects at last follow-up, without severe hypoglycemic episode or diabetes-related mortality. TP-IAT should be further considered in light of the latest evidence of the impact of POPF on the long-term outcome 40,41. In fact, TP may prevent a long-lasting decline of patients’ general condition associated with CR-POPF.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies are in agreement with these results [48]. In a recent systematic review on the impact of POPF on long-term outcomes, only one study among sixteen found lower overall survival for patients with POPF [49]. Most of these studies used a Cox regression model, which does not take into account the baseline risk or the variation in mortality risk over time.…”
Section: Discussionmentioning
confidence: 67%
“…Clinically relevant postoperative pancreatic fistula (CR-POPF) is a feared complication following pancreatoduodenectomy that negatively impacts short- and long-term outcomes 1 , 2 . Accurate risk stratification of CR-POPF in the preoperative setting can assist in determining the best surgical approach for high-risk or frail patients.…”
Section: Introductionmentioning
confidence: 99%